S1_1 A Floating World - Madden, Shannon; Mahmood, Ridda; Gajendran, Arcchana (Physics Special Topics, 2017)
As in the film 2012, we proposed geological disasters to cause global flooding in the year 2030 causing human survival to depend on arks for one year. We calculated the size of the three arks needed to be 12612 m x 4204 m x 4204 m to support the weight of the projected population size and its food supply. Using Archimedes’ Principle, we concluded the arks will be of sufficient buoyancy, sitting at a depth of 51.5 m in the water.